Tephritidae flies associated with Chuquiraga avellanedae (Asteraceae) in Patagonia, Argentina - Martínez, Fernando Joaquín (2020)
In Patagonia, knowledge about the interaction among tephritids and the native flora is very scarce. In this study we identified for the first time two tephritid species (Cecidochares sp. and Neosphaeniscus m-nigrum) associated with the capitula of Chuquiraga avellanedae. This is the first record of a host plant for the genus Neosphaeniscus. Cecidochares sp. was more abundant and had a shorter development time than N. m-nigrum. Also, two families of parasitoid wasps (Pteromalidae and Eurytomidae) were registered. Further studies are needed to understand the impact of these tephritids on C. avellanedae fitness and their potential to control its populations.